Electrochemical exploration of the effects of calcination temperature of a mesoporous zinc vanadate anode material on the performance of Na-ion batteries. Issue 10 (2nd July 2019) - Muruganantham, Rasu; Maggay, Irish Valerie Buiser; Juan, Lyn Marie Z. De; Nguyen, Mai Thanh; Yonezawa, Tetsu; Lin, Chia-Her; Lin, Yan-Gu; Liu, Wei-Ren
Abstract : As transition metal oxides are attractive candidates for energy storage applications, the spinel-structure of mesoporous ZnV2 O4 as a potential novel anode for Na-ion storage and the synergetic effects of calcination temperature were studied. Abstract : Nowadays, transition metal oxides are being rapidly developed for application as Na-ion storage anode materials, which provide a relatively high theoretical capacity compared to the graphitic anode; however, the evaluation of enhanced electrochemical performance of SIBs via various approaches, such as coating or doping, is an ongoing process. Hence, in this study, a mesoporus ZnV2 O4 anode material with a spinel structure was successfully synthesized via a solvothermal technique followed by calcination at different temperatures; moreover, the impact of the calcination temperature on the Na-ion storage performance of this anode material was thoroughly investigated for the first time. The initial discharge capacities of 178, 251, and 296 mA h g −1 were obtained for the cacination temperatures of 500, 600, and 700 °C, respectively; after 250 cycles, the ZVO-700 electrode retained the discharge capacity of 166 mA h g −1 at 200 mA g −1 with the high coulombic efficiency of 99%. Furthermore, ZVO-500 and ZVO-600 retained 55 mA h g −1 and 99 mA h g −1 with a ∼27% and ∼42% retention rate, respectively. The electrochemical Na-ion storage performance is predicted by the conversion reaction of ZnV2 O4 . Moreover, the ZVO-700 sample showed higher surface area and pore volume, which led to remarkable electrochemical performance, than the ZVO-500 and ZVO-600 samples.